Active Front Steering Controller Design with Side Slip Angle Free Model Matching Approach - Sever, Mert; Arslan, M. Selcuk (IEEE, 2018)
A side slip angle free model matching controller (MMC) is designed to improve vehicle yaw stability by active front steering. Optimization of controller gains is specified by a classical LQR problem. Additionally, LQR controller gains are structured to enable side slip angle free design. Design of an LQR having a structured controller gain is formulated as a convex optimization problem subject to linear matrix inequalities (LMIs) constraints. The proposed controller is designed with an augmented state space model including a linear bicycle model and model matching error dynamics. Superiority of the proposed controller is shown by numerically comparing with a classical full state feedback LQR. In order to obtain realistic results; a three-degrees-of-freedom nonlinear vehicle model is used. The nonlinear vehicle model is composed of lateral, yaw and longitudinal motions with the well-known Magic Formula tire model. Simulation results show that the proposed structured MMC provides very compatible performance with full state feedback LQR design.
Keywords: active front steering; model matching; linear matrix inequalities; linear quadratic regulator; YAW RATE; VEHICLE; SYSTEMS; Automation & Control Systems; Computer Science; Engineering